PENGARUH MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PT. BPR BANK SURYA YUDHA CABANG BOBOTSARI - Fatmawati, Tri; Barima, Hima; Handayani, Juli (JURNAL EKONOMI, 2024)
Banking is one of the vital sectors in a country's economy, which has an important role in allocating financial resources, supporting economic growth, and facilitating trade and investment activities. In Indonesia, the banking sector has experienced a significant transformation in line with economic developments and regulatory changes. Since its inception, banking in Indonesia has experienced various stages of evolution, from its initial role as a lender and depositor of funds to becoming the main pillar in the national financial system. The aim of this research is to examine the influence of motivation and work environment on the performance of PT employees. BPR BANK SURYA YUDHA, Beratan branch. The type of research method used is a quantitative method, questionnaire data from 53 respondents who came from PT employees. BPR BANK SURYA YUDHA, Beratan branch. The sampling technique uses stratified random sampling. Data was taken using a questionnaire which was measured using a Likert scale. This research uses multiple linear analysis with the help of the SPSS version 26 program. The results of this research show that motivation has no significant and positive effect on employee performance and the work environment has a significant and positive effect on employee performance and motivation and work environment simultaneously have a significant effect on employee performance.